2016
DOI: 10.1523/jneurosci.1902-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Vestibular Signals for the Control of Standing in Humans

Abstract: During standing balance, vestibular signals encode head movement and are transformed into coordinates that are relevant to maintaining upright posture of the whole body. This transformation must account for head-on-body orientation as well as the muscle actions generating the postural response. Here, we investigate whether this transformation is dependent upon a muscle's ability to stabilize the body along the direction of a vestibular disturbance. Subjects were braced on top of a robotic balance system that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 54 publications
8
78
0
Order By: Relevance
“…; Forbes et al. , ). Whether and how fear of falling influences these physiological control systems is currently debated (Horslen et al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Forbes et al. , ). Whether and how fear of falling influences these physiological control systems is currently debated (Horslen et al.…”
Section: Discussionmentioning
confidence: 97%
“…Forbes et al. () altered head yaw systematically and showed craniocentric modulation of muscle activities at short and medium latency. Mian and Day () altered stance width and head orientation and showed balance relevant modulation of response at short and medium latency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is a strong possibility that there is sufficient time, and that the cerebellum does indeed affect the response, particularly since our data showed that there was a trend for an increase. Even if the SL response does not travel through the cerebellum, it is likely the cerebellar output is still able to modulate the excitability of the vestibular nuclei, which would result in a change in SL response amplitude (Forbes et al., 2016). We may not have been able to detect significant changes in the SL response due to certain parameters of the experimental protocol, including the intensity of the stimulus and the postural orientation.…”
Section: Discussionmentioning
confidence: 99%
“…There is literature to suggest that the SL response may not be consistent or reliable when the vestibular stimulus is below 2 mA (Ali, Rowen, & Iles, 2003; Fitzpatrick et al., 1994). Additionally, the quality of the reflexes may have been compromised with head orientation, as the reflexes are obtainable [as evidenced by the results of our study and other experiments (Dakin, Son, Inglis, & Blouin, 2007; Day et al., 1997; Forbes et al., 2016; Nashner & Wolfson, 1974)], yet not as prominent in the soleus muscle with the head facing forward (Fitzpatrick et al., 1994). Most studies examining vestibular reflexes have subjects stand with their head facing over the shoulder (Britton et al., 1993; Fitzpatrick et al., 1994; Lund & Broberg, 1983; Nashner & Wolfson, 1974; Welgampola & Colebatch, 2001), however, we opted to test the reflexes with head forward as we have shown in a previous experiment that depressing the cerebellar vermis with cTBS can result in a modulation in the postural sway direction, such that it is no longer intra‐aural with the head facing over the shoulder (Lam et al., 2016).…”
Section: Discussionmentioning
confidence: 99%